Performance Evaluation of CSR in Supply Chains - Shyh-Hwang Lee (International Journal of Supply Chain Management, 2016)
Given a lack of studies that have explored the integration of Corporate Social Responsibility (CSR) management within supply chain operations reference (SCOR), the purpose of this study is to identify the discrepancies in how CSR management (CSRM) be incorporated into SCOR, including issues with the hierarchical representation of CSRM processes, metrics, best practices and skills. Therefore, this research aims to establish a performance evaluation framework with application of SCOR model using Fuzzy extended AHP method for evaluating CSR performances in supply chains. These may be potentially helpful for embedding CSRM within other supply chain management processes, visualizing CSR performance metrics in a supply chains performance hierarchy and integrating supply chain management with organisational enterprise CSRM.